Comparison of Cockcroft-Gault and Modification of Diet in Renal Disease Formulas as Predictors of Cardiovascular Outcomes in Patients With Myocardial Infarction Treated With Primary Percutaneous Coronary Intervention - ULUGANYAN, MAHMUT; Ekmekci, Ahmet; Uluganyan, MAHMUT; Gungor, Baris; Tufan, Fatih; Cekirdekci, Elif Iclal; Ozcan, Kazim Serhan; Erer, Hatice Betul; Orhan, Ahmet; Osmanov, Damir; Bozbay, Mehmet; Cicek, Gokhan; et al. (My University, 2014)
We prospectively assessed the value of estimated glomerular filtration rate (eGFR) by the Modification of Diet in Renal Disease (MDRD) and Cockcroft-Gault (C-G) equations in predicting inhospital adverse outcomes after primary coronary intervention for acute ST-segment elevation myocardial infarction. We classified 647 patients into 3 categories according to eGFR, <60, 60 to 90, and >90 mL/min/1.73 m2 . The eGFRC-G classified 17 patients in the >90 mL/min/1.73 m2 subgroup and 6 and 11 patients in the 60 to 90 and <60 mL/min/1.73 m2 subgroups, respectively. In multivariate analysis, patients with eGFRC-G < 60 mL/min/1.73 m2 had 19.5-fold (95% confidence interval [CI] 1.55-178) higher mortality risk and 5.48-fold (95% CI 1.75-24.21) higher major adverse cardiac events risk compared to patients with eGFRC-G >90 mL/min/1.73 m2 (P ¼ .01 and P ¼ .01, respectively); the eGFRMDRD was not predictive. Although the MDRD equation more accurately estimates GFR in certain populations, the CG formula may be a better predictor of adverse events.